2009
DOI: 10.1016/j.ejcts.2009.02.062
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of plantar hyperhidrosis after endoscopic thoracic sympathicolysis

Abstract: EBTS is followed by redistribution of body perspiration, with, and important, plantar anhydrosis and hypohidrosis. Although EBTS is the standard treatment for palmar primary hyperhidrosis, we must continue studying baseline sympathetic activity in patients affected by primary hyperhidrosis and the neuroanatomy of the sympathetic system to understand the redistribution of sweating and decrease of hyperhidrosis in the zones regulated by mental or emotional stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Although palmar hyperhidrosis is a the most common form of PH, plantar hyperhidrosis frequently accompanies palmar hyperhidrosis (1,8,9). There is no consensus regarding the management of plantar hyperhidrosis combined with palmar hyperhidrosis (8,(11)(12)(13)18,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although palmar hyperhidrosis is a the most common form of PH, plantar hyperhidrosis frequently accompanies palmar hyperhidrosis (1,8,9). There is no consensus regarding the management of plantar hyperhidrosis combined with palmar hyperhidrosis (8,(11)(12)(13)18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the upper thoracic sympathetic levels ranging from T2 to T5 by various methods are blocked according to the hyperhidrosis type, patient condition, and surgeon preference (5)(6)(7). Although palmar hyperhidrosis is a predominant form of PH, plantar hyperhidrosis also occurs in >50% of cases (1,8,9). When upper thoracic sympathetic blockage is performed for palmar hyperhidrosis accompanied by plantar hyperhidrosis, there is sometimes an improvement in plantar hyperhidrosis (10)(11)(12).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…We observed many patients with palmo-axillo-plantar HH reporting sustained and satisfactory improvement in plantar HH after TS. A literature review [3,4,7,8,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] revealed that the degree of improvement in plantar HH after TS varied according to the primary indication for and the level and method of TS (Supplemental Table 1).…”
Section: Commentmentioning
confidence: 99%
“…Palmo-axillo-plantar HH is considered a unique variant of primary HH that was presumed to be a hereditary autosomal-dominant disease with a familial incidence ranging from 12.5% to 56.5% [5,6]. Some studies estimated that palmo-plantar and palmo-axillo-plantar variants present in approximately 70% to 100% of patients with HH [7,8]. Excess plantar sweating represents an embarrassing problem to the patient and is usually treated with lumbar sympathectomy that is associated with technical difficulties, complications, such as retrograde ejaculation, and sometimes failure due to inadequate removal of the sympathetic chain [9].…”
mentioning
confidence: 99%